2011
DOI: 10.1055/s-0031-1273316
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostische Wertigkeit der transthorakalen Sonografie vergleichend zur Thoraxübersicht beim Nachweis eines postinterventionellen Pneumothorax

Abstract: Transthoracic ultrasound of the chest is a highly sensitive and specific diagnostic tool in the diagnosis of a pneumothorax. In comparison to chest radiography, it is better available and prevents administration of ionizing radiation. However, a disadvantage of ultrasound is the lack of quantification of a pneumothorax and the assessment of the indication for chest tube drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…Furthermore, a pneumothorax following transbronchial biopsy can be reliably excluded with US (sensitivity 100% and specificity 83%) [30]. Soldati et al [31] showed that US was superior to chest radiographs in diagnosing pneumothoraces following blunt chest trauma.…”
Section: Diagnostic Transthoracic Ultrasonographymentioning
confidence: 99%
“…Furthermore, a pneumothorax following transbronchial biopsy can be reliably excluded with US (sensitivity 100% and specificity 83%) [30]. Soldati et al [31] showed that US was superior to chest radiographs in diagnosing pneumothoraces following blunt chest trauma.…”
Section: Diagnostic Transthoracic Ultrasonographymentioning
confidence: 99%
“…The use of chest ultrasound to diagnose pneumothorax has long been questioned. However, in recent years, numerous clinical trials have demonstrated that pneumothorax can reliably be detected by thoracic ultrasound with a high sensitivity (80-100%) and specificity (83-100%) [3,9,10,11,12,13,14,15]. Consequently, chest sonography has gained increased interest also in emergency medicine due to its high sensitivity (>90%) and specificity (99%) [10,13,15,16,17,18].…”
Section: Sonography and Sonomorphology Of Important Thoracic Emergenciesmentioning
confidence: 99%
“…Adding power color Doppler imaging improves this examination [10]. Further diagnostic criteria are absence of B-lines, absence of lung pulse (in M-mode or power color Doppler) and finally the detection of a lung point (fig.…”
Section: Sonography and Sonomorphology Of Important Thoracic Emergenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the literature [1,5,19,26,27,31,32], our study population is on the whole representative; however, the average age is slightly older in comparison, primarily due to the higher proportion of patients with post-interventional or postoperative pneumothorax (after pacemaker implantation, defibrillation or cardiac surgery).…”
mentioning
confidence: 99%